2013
DOI: 10.4238/2013.december.19.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phenotypic profile of subpopulations of peripheral blood leukocytes in European (Bos taurus taurus) and Zebu cattle (Bos taurus indicus)

Abstract: ABSTRACT. Differences in cellular and humoral immunity in Zebu (Bos taurus indicus) and European (B. taurus taurus) cattle breeds, which may be related to differences in resistance or susceptibility to infectious or parasitic diseases, are largely unknown. This study aimed to perform a comparative analysis of innate and adaptive immunity of European (including Holstein, Brown Swiss, and Hereford) and Zebu (including Gir, Nelore, and Guzera) breeds, by assessing their peripheral blood leukocyte profiles (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The findings of breed or type differences parallel results previously found for routine hematology (Gerber et al, 1975;Kieferndorf and Keller, 1990;Pomorska, 2013), leukocyte subsets (Macedo et al, 2013), differential haemograms, platelet-rich plasma production of growth factors (Giraldo et al, 2013), and inflammatory mediators, such as TNF␣ and IL-1 in response to in vivo stimuli (Wilmink et al, 2003). The two types of horses compared in the present study summarised different numbers of individuals of different breeds.…”
Section: Breed Is Relevant For Some Immunological Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of breed or type differences parallel results previously found for routine hematology (Gerber et al, 1975;Kieferndorf and Keller, 1990;Pomorska, 2013), leukocyte subsets (Macedo et al, 2013), differential haemograms, platelet-rich plasma production of growth factors (Giraldo et al, 2013), and inflammatory mediators, such as TNF␣ and IL-1 in response to in vivo stimuli (Wilmink et al, 2003). The two types of horses compared in the present study summarised different numbers of individuals of different breeds.…”
Section: Breed Is Relevant For Some Immunological Parameterssupporting
confidence: 89%
“…Influences of age, breed and sex on hematological parameters have been described for different species (Schalm et al, 1975;Mayr et al, 1979;Allen et al, 1984;Goto and Nishioka, 1989;Kieferndorf and Keller, 1990;Shiga et al, 1999;Čebulj-Kadunc et al, 2002Čebulj-Kadunc et al, , 2003Satué et al, 2009;Mikniene et al, 2014;Novotny et al, 2014), as well as for lymphocyte subset composition (Goto and Nishioka, 1989;Ohtsuka et al, 2002;Satué et al, 2010;Robbin et al, 2011;Macedo et al, 2013), innate immunity parameters (Krasimira et al, 2013), and cytokine serum/plasma levels or secretion in vitro (Bruunsgaard et al, 2001;Marik and Zaloga, 2001;Silberer et al, 2008;Fujiwara et al, 2012;Giraldo et al, 2013;Wray et al, 2013). Furthermore, circadian differences have been described for secreted cytokine levels (Pollmächer et al, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…Although resistance or susceptibility to disease involves multifactorial mechanisms, it has been reported that Zebu cattle tend to have a higher degree of natural resistance to diseases when compared to European cattle [ 27 - 31 ]. Analyzing the profile of peripheral blood leukocytes of different bovine breeds, we recently demonstrated that Guzerat cattle comparatively has increased levels of circulating leukocytes, especially monocytes, eosinophils, T lymphocytes (particularly CD4 + T cells) and non-B/non-T (NTNB) lymphocytes, with a decreased percentage of B lymphocytes, and consequent increase in the T/B and CD4 + /CD8 + ratio [ 29 ]. In another study, we compared the macrophage function of Zebu cattle with that of macrophages from European cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Immunophenotyping was performed using specific monoclonal anti-bovine cell receptor antibodies as previously described [ 29 ]. Briefly, these antibodies were tittered, and 1:15, 1:30, 1:60, and 1:120 dilutions were used for anti-CD4, anti-CD8, γδ T and anti-CD21 antibodies, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the viability of all immune cell populations [53] decreases, presumably caused by intrinsic factors (e.g., advanced cell age and depletion of energy reserves in the course of diapedesis) and adverse environmental factors in milk [54]. 46 [38] 35-43 [1] 52 [58] 13 [28] Lymphocytes 45-65 [55] 55 [56] 10-28 [59] 21 [38] 14-26 [1] 46 [28] Mammary epithelial cells 1-3 [1] <1 [38] Table 3. Published data on the proportions of different lymphocyte subsets in peripheral blood and raw milk of healthy cows.…”
Section: Similarities Between Differential Cell Counts In Milk and Bl...mentioning
confidence: 99%